Social Media Use in Adolescents With Functional Abdominal Pain - Eshan Samuel; Sharmistha Lahiri; Syed Hashmi; Fernando Navarro (Frontiers Media S.A., 2020)
Social media use is increasing in children in the U.S., which could be related to the high prevalence of functional gastrointestinal disorders in this population.Objective: To investigate the relationship of social media use with the severity of gastrointestinal symptoms in patients with a functional abdominal pain or irritable bowel syndrome diagnosis.Study Design: We administered a questionnaire to collect information about screen time, demographics, and a modified Validated Varni PedsQL Gastrointestinal symptom scale which assesses the severity of gastrointestinal (GI) symptoms.Results: We surveyed a total of 59 subjects, which included 26 subjects with functional abdominal pain and 33 age-matched healthy controls. The median score across all 8 scales was about a third less for cases (median: 63; IQR: 55-78) than controls (median: 93; IQR: 83-95) (p < 0.001). Mean screen time in the study group (341 min/day) was very similar to that in the control group (331 min/day). There was no statistically significant association between screen time per day and the number of platforms used for either the cases or controls. YouTube (92%) and Instagram (88%) were the first and second most popular platforms used by the children with functional abdominal pain; Instagram (97%) and Snapchat (82%) were the most popular platforms in the healthy controls. Interestingly, social media were more often used for entertainment, reading, and productivity by the children with functional abdominal pain (p < 0.05).Conclusion: The amount of screen time/day and the number of social media platforms used does not correlate with the severity of abdominal pain and other GI symptoms in adolescents with FGID. Further research will be needed to confirm if the platforms are used differently by children with functional gastrointestinal disorder.